PENINGKATAN KOMPETENSI PROFESIONAL KONSELOR DALAM APLIKASI INSTRUMENTASI MELALUI LAYANAN PENGUASAAN KONTEN (PENELITIAN TINDAKAN LAYANAN DI SMP DAN MTS SE-KOTA PADANG PANJANG) - DASRIL DASRIL (Ta'dib, 2013)
The aim of this research was to describe and improve a professional councellor’s competency in applying the instrument of AUM PTSDL through services of content mastery. This research was an action research. The subject of this research were 20 junior high school councellors  who were accomodated in MGMP (Musyawarah Guru Pembimbing) in Padang Panjang regency. This research applied cyclical process that consisted of some cycles. Therefore, in this research plan, action, observation, and reflection were done in two cycles depended on the achievement of the research objective. The result of this research showed that services of content mastery could improve the councellors’ competency in applying the instrument of AUM PTSDL.Kata kunci: kompetensi profesional, aplikasi instrumentasi, guru pembimbing, layanan penguasaan konten